Evaluating the Service Performance of Heavy Axle Load Ballasted Railway by Using Numerical Simulation Method - Shuang Tian; Xianzhang Ling; Ting Li; Andrew Chan; Ionut-Razvan Georgescu (Applied Sciences, 2022)
To evaluate the service performance of the track substructure of heavy axle load (HAL) railway transportation, an inverse analysis was performed to estimate the resilient modulus values of the track substructure, based on the deflection data obtained from light falling weight deflectometer testing. Subsequently, a three-dimensional finite element model was developed to simulate the effect of the train speeds (v) and axle loads (F) on the typical dynamic responses in the railway track system. The results convincingly indicated that increasing v or F can amplify the track vibration. Finally, a critical stress ratio method was adopted to evaluate the service performance based on the numerical results. A recommended range of v and F was determined to maintain the long-term stability of the HAL railway line. The findings can provide guidance for designing the track and maintenance plans to avoid track support failures and ensure track infrastructure resiliency.